Biocompatibility, Cytotoxicity, and Antibacterial Evaluation of Novel Chitosan-Based 3D Bioprinted Bone Scaffolds: In Vitro Study - Arumugam, Parkavi (2026)
The objective of the study was the biologic characterisation of novel three dimensional (3D) bioprinted osseous scaffolds developed for bone tissue engineering, using biocompatibility, cytotoxicity analysis and antibacterial assay. A composite bioink comprising polyethylene glycol (PEG), polyethylene glycol diacrylate (PEGDA), hydroxyapatite (HAP), collagen (COL), and chitosan (CH)was formulated and 3D bioprinted into osseous scaffolds using Cellink Bio X, extrusion-based 3D bioprinter. In vitro biologic characterisation included 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay for biocompatibility using MG-63 osteoblast-like cells, cytotoxicity analysis using zebrafish model, with Group A (3D bioprinted scaffolds) and Group B (Phosphate buffer saline). Antibacterial assay was performed using disc diffusion method, with Group A1(low concentration of 3D bioprinted scaffolds), Group A2 (high concentration of 3D bioprinted scaffolds), Group B (dimethyl sulfoxide), and Group C (20 mg Erythromycin and 20 mg Penicillin) against Staphylococcus aureus (S. aureus, MTCC 740), Streptococcus mutans (S. mutans, MTCC 890), Enterococcus faecalis (E. faecalis, MTCC 439), and Klebsiella pneumoniae (K. pneumoniae, MTCC 109). Biologic characterisation revealed good biocompatibility of Group A (3D bioprinted scaffolds) comparable to Group B (untreated MG63), at all time points. No significant difference in embryo viability was observed for both Groups A and B, with good length, prominent trunk, tail, and organ development. Antibacterial assay revealed significant intergroup activity across all tested strains (p = 0.000), with comparable zone of inhibition of Group A2 with the control against S. aureus and S. mutans.  The biologic characterization of the novel 3D bioprinted osseous scaffolds revealed good biocompatibility, limited cytotoxicity, and promising antibacterial properties. These findings underscore the potential of the developed constructs for application in bone tissue engineering for enhancing overall health. Future studies should focus on osteogenic differentiation, mineralization, and in vivo performance.